Management of solitary fibrous tumours of the pleura: a systematic review and meta-analysis. Issue 3 (17th August 2020) - Mercer, Rachel M.; Wigston, Charlotte; Banka, Radhika; Cardillo, Giuseppe; Benamore, Rachel; Nicholson, Andrew G.; Asciak, Rachelle; Hassan, Maged; Hallifax, Robert J.; Wing, Louise; Bedawi, Eihab O.; Maskell, Nick A.; et al.
Background: Solitary fibrous tumours of the pleura (SFTP), or pleural fibromas, are rare tumours that generally, but not universally, follow a benign course. Surgical resection is the standard treatment, but there are no evidence-based guidelines regarding the management of these tumours. Methods: Five databases were searched from inception to April 1, 2019 for studies reporting on SFTP management. Results: Twenty-seven studies met the inclusion criteria (1542 patients, all non-comparative case series); 98% of these patients underwent resection and all SFTP included were pathologically diagnosed. 394 out of 1299 cases (30.5%, 95% CI 27.8–32.8%) were malignant with recurrence rates of between 0% and 42.9%. A pleural effusion was always associated with a negative outcome, but no other features were consistently reported to have negative associations. Preoperative biopsies incorrectly reported malignant histology in two studies. Over 25% of cases of recurrence occurred when a complete (R0) resection had been achieved. The first recurrence occurred >5 years after the initial resection in at least 23% of cases. Conclusions: There is strong evidence to support long-term surveillance after surgical resection of SFTP, even where a complete (R0) resection has been achieved; however, there is no clear evidence to inform clinicians regarding the selection of patients who should undergo resection. The rates of malignant SFTP and SFTP recurrence are higher than previously reported. Only those that were pathologically diagnosed or resected were included, which may bias the data towards more aggressive tumours. Data collection on radiologically diagnosed SFTP is required to draw conclusions regarding the timing and need for intervention. Long-term surveillance should be undertaken after a resection of solitary fibrous tumours of the pleura but further work is needed to determine which patients are likely to follow a malignant clinical course to decide timing and necessity of a resection https://bit.ly/2U10SaA